Efek latihan kalistenik selama delapan minggu terhadap kualitas kebugaran fisik terpilih dan kinerja keterampilan dalam bola tangan. - Fenta, Belaynesh Getnet; Mola, Dessalegn wase (Universitas Nusantara PGRI Kediri, 2023)
This study aimed to investigate the effect of eight-week callisthenics exercises on selected physical fitness qualities and skill performance in U-17 female handball players. The study utilized a quantitative research approach with an experimental design to achieve its goals. For this study, 20 female handball players were selected. The researcher employed a comprehensive sampling technique and randomly divided them into two equal groups: the experimental group (n = 10) and the control group (n = 10). During 8 weeks, the experimental group did callisthenics workouts three times weekly, while the control group stuck to regular handball training. The study assessed passing accuracy, dribbling speed, agility, and muscular strength in both groups before and after. The data collected from the participants were analyzed using SPSS version 24 software, employing paired sample t-tests and independent-sample t-tests with a significance level set at 0.05. The analysis revealed that callisthenics exercises significantly improved passing accuracy, speed dribble, agility, and muscular strength in the pre-post test of the experimental group (p<0.05). However, no significant differences were found in any control group variables (p > 0.05). Based on these findings, the eight-week callisthenics exercise program contributes to enhancing agility, muscular strength, passing accuracy, and speed dribbling in U-17 female handball project players.